2022
DOI: 10.3390/cancers14184416
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy as a Form of Nonpharmacologic Pain Modulation in Patients with Cancer: A Systematic Review of the Current Literature

Abstract: Aims and Objectives: To consolidate and summarize the current literature surrounding the use of music therapy as an effective noninvasive adjunct to conventional cancer therapy, especially as a low-risk alternative for pain management and anesthetic use in cancer patients. Background: Current studies have proposed that music therapy may be effective as a noninvasive adjunct to conventional cancer therapy in managing numerous outcomes in cancer patients. However, the findings of these investigations have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(215 reference statements)
1
6
0
Order By: Relevance
“…Among the four studies measuring anxiety as an outcome, three studies (75%) showed that MT reduced anxiety. The results are consistent with previous systemic reviews and meta-analyses [ 29 , 41 , 42 , 43 ]. This review only includes RCTs with participants who had CRC or gastrointestinal cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the four studies measuring anxiety as an outcome, three studies (75%) showed that MT reduced anxiety. The results are consistent with previous systemic reviews and meta-analyses [ 29 , 41 , 42 , 43 ]. This review only includes RCTs with participants who had CRC or gastrointestinal cancer.…”
Section: Discussionsupporting
confidence: 93%
“…This review only includes RCTs with participants who had CRC or gastrointestinal cancer. The other systemic reviews [ 29 , 41 , 42 , 43 ] include all types of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Psychosocial care is one of the important approaches for cancer survivors to alleviate negative emotions and psychological symptoms like anxiety and depression. 10,11 Psychosocial care commonly includes cognitive behavioral therapy (CBT), 12 mindfulness therapy, 13 music therapy, 14 and reminiscence therapy (RT), 15 and others. RT, a common method of social psychological intervention, mainly refers to discussing past activities, events, and experiences under some tangible cues (such as photos, familiar objects, music, and recordings).…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence suggests that music is indeed beneficial for different types of pain ( 13 , 14 , 18 , 19 ), in addition to psychological distress, ranging from smaller-scale mood improvements to anxiety disorders ( 20 ). Music can also improve the management of chronic pain conditions, such as cancer by reducing pain and its associated components of anxiety, depression, and quality of life ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Music is easy to implement in clinical contexts as it is safe, noninvasive, and inexpensive (3,4). Multiple clinical environments can be found using music today (5,6) for conditions such as childbirth (7)(8)(9)(10), resuscitation (11), cardiac surgery (12,13), cancer (14,15), in cardiology, during a catheter installation (16), or cataract surgery (17).…”
Section: Introductionmentioning
confidence: 99%